PERANCANGAN MUSEUM SEJARAH ISLAM NUSANTARA DENGAN PENERAPAN ARSITEKTUR NUSANTARA DI JAKARTA BARAT - Bella Cristy Yusnia; Putri Suryandari; Tri Endangsih (MAESTRO, 2020)
Abstract The Museum of Islamic History of the Archipelago is an answer to the problem of the differences between Islamic groups in the archipelago. So that the museum can provide information to the public about how Islam came to the archipelago peacefully without military support, both politics, solely preaching and also trading, then they marry local residents. Provide information to the public that our country is a unity between Indonesian and Islamic. Nusantara Architecture is an architectural art that focuses on the potential of culture, tradition, and climate conditions in the Indonesian archipelago. To support the concept of the Nusantara Islamic History Museum building, it will use the concept of Archipelago Architecture which will strengthen the characteristics of every diversity that exists in the archipelago and can provide education to visitors about the importance of knowing the cultural diversity of this country of Indonesia.